The mediation role of financial literation in ensuring MSMEs sustainability: An organizational characteristics perspective - Arik Prasetya; Kusdi Rahardjo; Mukhammad Kholid Mawardi; Raden Rustam Hidayat; Yudha Prakasa (University of Islam Malang, 2021)
The Micro, Small, and Medium Enterprise (MSMEs) sector has been recognized as an essential contributor to the economic development of Indonesia. However, the sustainability of MSMEs in Indonesia is still relatively low compared to the rest of ASEAN countries with similar levels of economic growth. This study aims to extend previous studies on the relationship between MSMEs characteristics and their sustainability by specifically including financial literation as a mediation role. This study used proportional random sampling as a sampling technique. A total of 191 MSMEs owner-managers questionnaire data were processed by using Partial Least Square analysis. This study confirmed the positive influence of MSMEs characteristics on financial literacy and financial literacy on the sustainability of MSMEs. Moreover, financial literation proves to be a significant mediator of MSMEs sustainability. This study suggests that MSMEs owner-managers need to be financially literate as it can enable them to make a good financial decision that can ensure their business sustainability.